Secondary battery and electric device

CN119137761APending Publication Date: 2024-12-13CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202280095096.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

It is difficult for existing secondary batteries to balance high energy density and service life when improving dynamic performance, and increasing energy density often affects dynamic performance and service life.

Method used

By using a combination of a first carbon-based material and a second carbon-based material in the negative electrode film layer, the first carbon-based material has a pore structure and the ID/IG is smaller than the ID/IG of the second carbon-based material, and its performance in the negative electrode film layer is adjusted The distribution can improve the compaction density and active ion transmission performance, ensuring that the secondary battery has good kinetic performance and storage performance under the premise of high energy density.

Benefits of technology

It realizes that the secondary battery has good kinetic performance and storage performance under the premise of high energy density, reduces the occurrence of side reactions, and improves the cycle performance and first Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137761A_ABST
    Figure CN119137761A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and a power utilization device, a negative electrode piece of the secondary battery comprises a negative electrode current collector and a negative electrode film layer, the negative electrode film layer has a first surface far away from the negative electrode current collector and a second surface opposite to the first surface, the thickness of the negative electrode film layer is marked as H, the area from the second surface of the negative electrode film layer to the thickness range of 0.3 H is marked as the first area of the negative electrode film layer, the area from the first surface of the negative electrode film layer to the thickness range of 0.3 H is marked as the second area of the negative electrode film layer, the first area comprises a first active material, and the second area comprises a second active material; the first active material includes a first carbon-based material, the second active material includes a second carbon-based material, the first carbon-based material has a pore structure, and the ID / IG of the first carbon-based material is less than the ID / IG of the second carbon-based material. According to the invention, the secondary battery has good dynamic performance and storage performance on the premise of high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Secondary batteries and electrical devices Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. As the scope of secondary battery applications expands, so too have the increasing demands placed on their performance. For example, the requirement for secondary batteries to balance various performance requirements, such as energy density, dynamic performance, and service life, has become increasingly challenging. However, existing technologies face the following challenges: improving the dynamic performance of secondary batteries often struggles to balance their energy density; and increasing their energy density often compromises their dynamic performance and service life.

[0003] Summary of the Invention

[0004] The present application is developed in view of the above-mentioned technical problems, and its purpose is to provide a secondary battery and an electrical device, which can enable the secondary battery to have good dynamic performance and storage performance while having high energy density.

[0005] According to a first aspect of the present application, a secondary battery is provided, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer having a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is denoted as H, the region within a thickness range from the second surface of the negative electrode film layer to 0.3H is denoted as the first region of the negative electrode film layer, the region within a thickness range from the first surface of the negative electrode film layer to 0.3H is denoted as the second region of the negative electrode film layer, the first region comprises a first active material, the second region comprises a second active material, the first active material comprises a first carbon-based material, the second active material comprises a second carbon-based material, the first carbon-based material has a pore structure, and the I of the first carbon-based material is 0.3H. D / I G Less than the I of the second carbon-based material D / I G , I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at .

[0006] The inventors found that by making the first region of the negative electrode film layer include a first carbon-based material, the second region includes a second carbon-based material, the first carbon-based material has a pore structure, and the I of the first carbon-based material is D / I G Less than the I of the second carbon-based material D / I G , which can make the negative electrode sheet have high compaction density, high active ion transport performance and high surface stability, thereby enabling the secondary battery to have good dynamic performance and storage performance while having high energy density.

[0007] In any embodiment of the present application, the first carbon-based material I D / I G With the second carbon-based material I D / I G The ratio A is less than or equal to 0.80, and can be selected from 0.32 to 0.77. When α is within the above range, it is beneficial for the secondary battery to better balance good dynamic performance and storage performance while having high energy density.

[0008] In any embodiment of the present application, the first carbon-based material I D / I G The first carbon-based material has an I of 0.152-0.280, and can be optionally 0.155-0.220. D / I G Within the above range, the first carbon-based material may have less disordered carbon, higher specific capacity and higher chemical stability, thereby reducing the occurrence of side reactions and improving the energy density and storage performance of the secondary battery.

[0009] In any embodiment of the present application, the second carbon-based material I D / I G The second carbon-based material has an I of 0.230-0.500, and can be optionally 0.235-0.450. D / I G When within the above range, the active ion transport performance of the second carbon-based material is better, which is beneficial to improving the kinetic performance of the secondary battery.

[0010] In any embodiment of the present application, the volume distribution particle size Dv50 of the second carbon-based material is smaller than the volume distribution particle size Dv50 of the first carbon-based material. This facilitates the first region and the second region of the negative electrode film layer to have a suitable pore distribution, thereby increasing the compaction density of the negative electrode film layer and the energy density of the secondary battery. On the other hand, it can also improve the electrolyte infiltration and retention properties of the negative electrode film layer and reduce the expansion of the negative electrode sheet, thereby further improving the storage performance and / or cycle performance of the secondary battery.

[0011] In any embodiment of the present application, the powder compaction density of the second carbon-based material under a pressure of 20,000 N is less than the powder compaction density of the first carbon-based material under a pressure of 20,000 N. By adjusting the powder compaction density of the second carbon-based material to be less than the compaction density of the first carbon-based material, on the one hand, it is beneficial to improve the energy density of the secondary battery, and on the other hand, it is beneficial to have a suitable pore distribution in the first region and the second region of the negative electrode film layer, thereby improving the wetting and retention characteristics of the negative electrode film layer for the electrolyte, thereby improving the dynamic performance and / or cycle performance of the secondary battery.

[0012] In any embodiment of the present application, the second carbon-based material includes at least one of artificial graphite and natural graphite; optionally, the second carbon-based material includes natural graphite.

[0013] In any embodiment of the present application, the X-ray diffraction pattern of the first carbon-based material does not have a diffraction peak of the 3R phase 012 crystal plane. As a result, the first carbon-based material particles have fewer internal defects, which can further reduce the occurrence of side reactions, reduce the irreversible consumption of active ions, and improve the initial coulombic efficiency and storage performance of the secondary battery.

[0014] In any embodiment of the present application, the second carbon-based material has a diffraction peak of the 012 crystal plane of the 3R phase in the X-ray diffraction pattern.

[0015] In any embodiment of the present application, the second carbon-based material has a porous structure.

[0016] In any embodiment of the present application, the second carbon-based material includes one or more pores with an area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 pore structure.

[0017] In any embodiment of the present application, the ratio of the pore area in the cross-section of the first carbon-based material particle to the cross-sectional area of ​​the first carbon-based material particle is recorded as α1, and the ratio of the pore area in the cross-section of the second carbon-based material particle to the cross-sectional area of ​​the second carbon-based material particle is recorded as α2, and α1<α2.

[0018] In any embodiment of the present application, the first carbon-based material includes one or more pores with an area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2When the first carbon-based material includes a pore structure having the above-mentioned pore area, the pore structure can reserve the required expansion space for its particle volume change, thereby further reducing the risk of particle breakage and generation of new interfaces, thereby reducing the occurrence of side reactions and improving the storage performance of the secondary battery.

[0019] In any embodiment of the present application, the first carbon-based material includes an outer region and an inner region located inside the outer region, wherein the outer region refers to a region extending from the surface of the first carbon-based material particle to the interior of the particle by a distance of 0.25L, where L refers to the minor axis length of the first carbon-based material particle, the total pore area of ​​the outer region is denoted as S1, the total pore area of ​​the inner region is denoted as S2, and S2>S1. When the first carbon-based material further satisfies S2>S1, the first coulombic efficiency of the secondary battery can be improved, and the storage performance and / or cycle performance of the secondary battery can be further improved.

[0020] In any embodiment of the present application, 1.5≤S2 / S1≤500, optionally, 2≤S2 / S1≤450. When S2 / S1 is also within the above range, the secondary battery can better achieve both high energy density and good storage performance.

[0021] In any embodiment of the present application, the area of ​​the pore structure in the outer region of the first carbon-based material is less than or equal to 0.2 μm 2 , can be selected to be less than or equal to 0.10μm 2 By controlling the area of ​​the pore structure in the outer region of the first carbon-based material within the above range, the outer region of the first carbon-based material can have a dense structure, thereby effectively improving the structural stability of the first carbon-based material, avoiding the electrolyte from penetrating into the pore structure inside the first carbon-based material particles as much as possible, reducing the occurrence of side reactions, and effectively improving the storage performance of the secondary battery.

[0022] In any embodiment of the present application, the inner region of the first carbon-based material includes one or more areas greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 By including the aforementioned pore structure in the interior of the first carbon-based material, the rolling pressure of the negative electrode sheet can be effectively reduced, effectively reducing particle damage, and reserving sufficient and stable expansion space for the volume change of the first carbon-based material particles, thereby reducing the risk of first carbon-based material particle breakage. Furthermore, the compaction density of the negative electrode film layer can be increased, thereby improving the energy density of the secondary battery.

[0023] In any embodiment of the present application, the first carbon-based material and / or the second carbon-based material include primary particles. The first carbon-based material contains an appropriate proportion of primary particles, which can give it a higher structural stability and reduce the occurrence of side reactions, thereby improving the storage performance of the secondary battery. In addition, it can also increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery. The second carbon-based material contains an appropriate proportion of primary particles, which can give it a higher structural stability and reduce side reactions, thereby improving the storage performance of the secondary battery. In addition, it can also increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery.

[0024] In any embodiment of the present application, the number of the primary particles in the first carbon-based material accounts for greater than or equal to 50%.

[0025] In any embodiment of the present application, the number of the primary particles in the second carbon-based material accounts for greater than or equal to 50%.

[0026] In any embodiment of the present application, at least a portion of the surface of the first carbon-based material and / or the second carbon-based material has a coating layer; optionally, the coating layer includes carbon.

[0027] In any embodiment of the present application, the specific surface area of ​​the first carbon-based material is less than or equal to 2.1 m 2 / g, optional 1.1m 2 / g-2.0m 2 The first carbon-based material has a lower specific surface area, thereby reducing the consumption of active ions by SEI film formation and improving the initial coulombic efficiency and storage performance of the secondary battery.

[0028] In any embodiment of the present application, the volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm, and can be optionally 10.0 μm-22.0 μm.

[0029] In any embodiment of the present application, the volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-45.0 μm, and can be optionally 16.5 μm-42.0 μm.

[0030] When the volume distribution particle size Dv50 and / or Dv90 of the first carbon-based material is within the above range, it is beneficial to improve the transmission performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the first carbon-based material, reduce the occurrence of side reactions, and improve the storage performance of the secondary battery.

[0031] In any embodiment of the present application, the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is ≤1.55, and can optionally be 0.90-1.50. When the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is within the above range, its particle packing performance is good, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial to adjust the pore distribution of the negative electrode film layer and improve the dynamic performance of the secondary battery.

[0032] In any embodiment of the present application, the powder compaction density of the first carbon-based material under a pressure of 20,000 N is 1.65 g / cm 3 -2.0g / cm 3 , optional 1.68g / cm 3 -1.98g / cm 3 When the powder compaction density of the first carbon-based material is within the above range, the compaction density of the negative electrode film layer can be increased, thereby increasing the energy density of the secondary battery. This is also conducive to forming a reasonable pore structure between the particles of the negative electrode film layer, thereby improving the active ion and electron transport performance, and thus improving the kinetic performance of the secondary battery.

[0033] In any embodiment of the present application, the tap density of the first carbon-based material is 0.85 g / cm 3 -1.30g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 When the tap density of the first carbon-based material is within the above range, it can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery. It is also conducive to forming a reasonable pore structure between the particles of the negative electrode film layer, improving the active ion and electron transport performance, and thus improving the kinetic performance of the secondary battery.

[0034] In any embodiment of the present application, the graphitization degree of the first carbon-based material is ≥95.5%, and can be optionally 95.5%-98.0%, thereby facilitating improvement of the energy density of the secondary battery.

[0035] In any embodiment of the present application, the gram capacity of the first carbon-based material is ≥355 mAh / g, and can be optionally 355 mAh / g-370 mAh / g, thereby facilitating improvement of the energy density of the secondary battery.

[0036] In any embodiment of the present application, the X-ray diffraction pattern of the first carbon-based material has a diffraction peak of the 3R phase 101 crystal plane. As a result, there may be more active sites on the surface of the first carbon-based material, which is conducive to the rapid deintercalation of active ions.

[0037] In any embodiment of the present application, the adsorption capacity of linseed oil by 100g of the first carbon-based material is 30ml-47mL. When the adsorption capacity of linseed oil by the first carbon-based material is within the above range, it is beneficial to improve the storage performance and / or dynamic performance of the secondary battery.

[0038] In any embodiment of the present application, the specific surface area of ​​the second carbon-based material is greater than or equal to 1.8 m 2 / g, optional 1.9m 2 / g-3.5m 2 When the specific surface area of ​​the second carbon-based material is within the above range, it is beneficial to reduce the occurrence of side reactions and reduce the consumption of active ions by SEI film formation, thereby enabling the secondary battery to have both high initial coulombic efficiency and good cycle performance and storage performance.

[0039] In any embodiment of the present application, the Dv50 of the second carbon-based material is 8.0 μm-15.0 μm, and can be optionally 10.0 μm-15.0 μm. When the volume distribution particle size Dv50 of the second carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the second carbon-based material, reduce the occurrence of side reactions, and improve the storage performance of the secondary battery.

[0040] In any embodiment of the present application, the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is ≤1.65, and can be optionally 0.90-1.65. When the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is within the above range, its particle packing performance is good, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial to adjust the pore distribution of the negative electrode film layer and improve the dynamic performance of the secondary battery.

[0041] In any embodiment of the present application, the powder compaction density of the second carbon-based material under a pressure of 20000N is 1.60g / cm 3 -1.95g / cm 3 , optional 1.65g / cm 3 -1.92g / cm 3 When the powder compaction density of the second carbon-based material is within the above range, the compaction density of the negative electrode film layer can be increased, thereby increasing the energy density of the secondary battery. This is also conducive to forming a reasonable pore structure between the particles of the negative electrode film layer, thereby improving the active ion and electron transport performance, and improving the electrolyte infiltration and retention characteristics of the negative electrode film layer, thereby improving the kinetic performance and / or cycle performance of the secondary battery.

[0042] In any embodiment of the present application, the tap density of the second carbon-based material is 0.85 g / cm 3 -1.25g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 When the tap density of the second carbon-based material is within the above range, it can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery. It is also conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, improving the active ion and electron transport performance, and improving the negative electrode film layer's electrolyte infiltration and retention characteristics, thereby improving the kinetic performance of the secondary battery.

[0043] In any embodiment of the present application, the degree of graphitization of the second carbon-based material is 94.5%-98.0%, and optionally 95.0%-97.5%. When the degree of graphitization of the second carbon-based material is within the above range, it is beneficial to improve the active ion transport performance of the negative electrode film layer and also to improve the negative electrode capacity, thereby enabling the secondary battery to have both high energy density and good kinetic performance.

[0044] In any embodiment of the present application, the gram capacity of the second carbon-based material is 355 mAh / g-372 mAh / g, and optionally 356 mAh / g-370 mAh / g. When the gram capacity of the second carbon-based material is within the above range, on the one hand, the energy density of the secondary battery can be improved, and on the other hand, the second carbon-based material can also have good active ion transport performance, thereby also helping to improve the kinetic performance of the secondary battery.

[0045] In any embodiment of the present application, the second carbon-based material has a diffraction peak of the 3R phase 101 crystal plane in its X-ray diffraction pattern.

[0046] In any embodiment of the present application, the first active material further includes a third carbon-based material, wherein the third carbon-based material includes artificial graphite having a primary particle morphology. The combination of the first and third carbon-based materials facilitates the negative electrode film layer to have a suitable pore structure and enhances the active ion transport performance of the negative electrode film layer.

[0047] In any embodiment of the present application, the surface of the artificial graphite in the primary particle morphology does not have a carbon coating layer. The artificial graphite in the primary particle morphology has a relatively stable surface. When the surface does not have a carbon coating layer, it is beneficial to maintain its low side reaction activity and reduce the occurrence of side reactions, thereby further improving the cycle performance and storage performance of the secondary battery.

[0048] In any embodiment of the present application, the mass proportion of the third carbon-based material in the first active material is less than or equal to 80 wt %, and can be optionally 20 wt %-70 wt %.

[0049] In any embodiment of the present application, the degree of graphitization of the third carbon-based material is 92.5%-95.5%, and optionally 92.7%-95.5%. When the degree of graphitization of the third carbon-based material is within the above range, it is beneficial to improve the active ion transport performance of the negative electrode film layer, especially the first region, thereby facilitating the secondary battery to achieve both high energy density and good kinetic performance.

[0050] In any embodiment of the present application, the powder OI value of the third carbon-based material is 4.5-11.5, and can be optionally 4.5-11.0. The powder OI value of the third carbon-based material is relatively low, and the particles have active ion insertion ports in all directions, which is conducive to quickly receiving active ions from the positive electrode, thereby further improving the kinetic performance of the secondary battery.

[0051] In any embodiment of the present application, the particle size distribution (Dv90-Dv10) / Dv50 of the third carbon-based material is ≤1.65, and can be optionally 0.90-1.65. When the particle size distribution (Dv90-Dv10) / Dv50 of the third carbon-based material is within the above range, its particle packing performance is good, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial to adjust the pore distribution of the negative electrode film layer and improve the dynamic performance of the secondary battery.

[0052] In any embodiment of the present application, the volume distribution particle size Dv50 of the third carbon-based material is 12.0 μm-22.0 μm, optionally 13.5 μm-20.0 μm. When the volume distribution particle size Dv50 of the third carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the third carbon-based material, reduce the occurrence of side reactions, and improve the storage performance of the secondary battery.

[0053] In any embodiment of the present application, the specific surface area of ​​the third carbon-based material is 1.0 m 2 / g-2.0m 2 / g, optional 1.05m 2 / g-1.95m 2 / g. The third carbon-based material has a lower specific surface area, which can reduce the consumption of active ions in SEI film formation, reduce the occurrence of side reactions, and improve the first coulombic efficiency and storage performance of the secondary battery.

[0054] In any embodiment of the present application, the tap density of the third carbon-based material is 0.95 g / cm 3 -1.25g / cm 3 , optional 1.00g / cm3 -1.25g / cm 3 When the tap density of the third carbon-based material is within the above range, it can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery. It is also conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, improving the active ion and electron transport performance, and thus improving the kinetic performance of the secondary battery.

[0055] In any embodiment of the present application, the gram capacity of the third carbon-based material is 350 mAh / g-363 mAh / g, and optionally 352 mAh / g-362 mAh / g. When the gram capacity of the third carbon-based material is within the above range, on the one hand, the energy density of the secondary battery can be increased, and on the other hand, the active ion transport performance of the negative electrode film layer can be improved, thereby also helping to improve the kinetic performance of the secondary battery.

[0056] In any embodiment of the present application, the first region and / or the second region further comprises a silicon-based material. The silicon-based material can improve the pore structure in the negative electrode film layer, facilitate electrolyte infiltration and retention, and enhance the dynamic performance of the secondary battery; it can also increase the negative electrode capacity, thereby further improving the energy density of the secondary battery.

[0057] In any embodiment of the present application, the first region and the second region both comprise a silicon-based material, and the mass proportion of the silicon-based material in the first region is less than or equal to the mass proportion of the silicon-based material in the second region. This is beneficial for improving the electrolyte wetting properties of the negative electrode film layer, improving the transport performance of active ions, and improving the cycling performance and / or kinetic performance of the secondary battery.

[0058] In any embodiment of the present application, the intermediate region between the first region and the second region includes the first active material and / or the second active material.

[0059] In any embodiment of the present application, the porosity of the negative electrode film layer is 18.0%-36.7%, and can be optionally 19.0%-34.0%. This is beneficial for the negative electrode film layer to have both high capacity and suitable pore structure, and further beneficial for the secondary battery to have both high energy density and good storage performance and dynamic performance.

[0060] In any embodiment of the present application, the compaction density of the negative electrode film layer is 1.45 g / cm 3 -1.90g / cm 3 , optional 1.50g / cm 3 -1.85g / cm 3This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good storage performance and kinetic performance.

[0061] In any embodiment of the present application, the surface density of the negative electrode film layer is 5.0 mg / cm 2 -25.0mg / cm 2 , optional 5.5mg / cm 2 -22.5mg / cm 2 This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good storage performance and kinetic performance.

[0062] In any embodiment of the present application, the OI value of the negative electrode film layer is less than or equal to 45.0, and can be optionally 8.0-45.0. This is beneficial for improving the active ion embedding performance of the negative electrode film layer and also for making the negative electrode film layer have a lower thickness rebound rate, thereby facilitating the secondary battery to have good storage performance and dynamic performance.

[0063] In any embodiment of the present application, the thickness of the negative electrode film layer is greater than or equal to 60 μm, and can be optionally 70 μm-250 μm.

[0064] A second aspect of the present application provides an electrical device comprising the secondary battery according to the first aspect of the present application.

[0065] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0067] FIG1 is a schematic diagram of an embodiment of a negative electrode sheet of the present application.

[0068] FIG2 is a schematic diagram of another embodiment of the negative electrode sheet of the present application.

[0069] FIG3 is a schematic diagram of another embodiment of the negative electrode sheet of the present application.

[0070] FIG. 4 is a schematic diagram of a cross-sectional image of a particle of the first carbon-based material of the present application.

[0071] FIG5 is a schematic diagram of an embodiment of a secondary battery of the present application.

[0072] FIG6 is an exploded schematic diagram of an embodiment of a secondary battery of the present application.

[0073] FIG7 is a schematic diagram of an embodiment of a battery module of the present application.

[0074] FIG8 is a schematic diagram of an embodiment of a battery pack of the present application.

[0075] FIG. 9 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 8 .

[0076] FIG. 10 is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source.

[0077] In the accompanying drawings, which are not necessarily drawn to scale, reference numerals are as follows: 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate, 10 negative electrode sheet, 101 negative electrode current collector, 102 negative electrode film layer, 102a first surface, 102b second surface, 1021 first region, 1022 second region, 1023 intermediate region, 200 first carbon-based material, 201 outer region, 202 inner region. DETAILED DESCRIPTION

[0078] Below, the embodiments of the secondary battery and the electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0079] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0080] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.

[0081] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.

[0082] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0083] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0084] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0085] Unless otherwise specified, the terms used in this application have the common meanings generally understood by those skilled in the art.

[0086] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0087] Unless otherwise specified, in this application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.

[0088] In this application, the terms "plurality" and "multiple" refer to two or more.

[0089] The inventors have discovered that the key to improving the kinetic performance of secondary batteries, especially their fast charging performance, lies in improving the kinetic performance of the negative electrode. Currently, most approaches to improving the kinetic performance of the negative electrode are by reducing the surface density of the negative electrode film or reducing the compaction density of the negative electrode film. However, numerous studies have shown that these methods of improving the kinetics of the negative electrode only improve the kinetic performance of the battery in the early stages of charging to a certain extent, and have no significant effect on improving the kinetic performance of the battery in the final stages of charging. This results in the secondary battery's kinetic performance failing to be effectively improved, and even makes it impossible to actually charge the secondary battery at a high rate. In addition, the energy density of the secondary battery will also be significantly reduced.

[0090] However, when the energy density of the secondary battery is increased by, for example, increasing the compaction density of the negative electrode film layer, the kinetic performance of the secondary battery is often deteriorated. In addition, the electrolyte wetting characteristics of the negative electrode film layer deteriorate under high compaction density, and the risk of negative electrode active material particles breaking increases, thereby increasing side reactions inside the battery, which in turn affects the storage performance of the secondary battery.

[0091] Therefore, it is difficult for current secondary batteries to achieve both high energy density and good dynamic and storage performance.

[0092] The inventors further conducted extensive research and cleverly improved the composition of the negative electrode film layer, breaking the above bottleneck.

[0093] Specifically, a first aspect of the embodiments of the present application provides a secondary battery.

[0094] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and released back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, and it can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes can also include an isolation membrane, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.

[0095] [Negative electrode]

[0096] Figures 1 to 3 are schematic diagrams of an embodiment of a negative electrode sheet of the present application. As shown in Figures 1 to 3, the negative electrode sheet 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101. The negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b disposed opposite the first surface 102a. The thickness of the negative electrode film layer 102 is denoted as H. The region within a thickness range of 0.3H from the second surface 102b of the negative electrode film layer is denoted as a first region 1021 of the negative electrode film layer. The region within a thickness range of 0.3H from the first surface 102a of the negative electrode film layer is denoted as a second region 1022 of the negative electrode film layer. The first region 1021 includes a first active material, and the second region 1022 includes a second active material. The first active material includes a first carbon-based material, and the second active material includes a second carbon-based material. The first carbon-based material has a pore structure, and the I of the first carbon-based material is 1. D / I G Less than the I of the second carbon-based material D / I G , I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The thickness H of the negative electrode film layer refers to the thickness of the negative electrode film layer located on one side of the negative electrode current collector.

[0097] The inventors found that by making the first region of the negative electrode film layer include a first carbon-based material, the second region includes a second carbon-based material, the first carbon-based material has a pore structure, and the I of the first carbon-based material is D / I G Less than the I of the second carbon-based materialD / I G , which can make the negative electrode sheet have high compaction density, high active ion transport performance and high surface stability, thereby enabling the secondary battery to have good dynamic performance and storage performance while having high energy density.

[0098] I of the second carbon-based material D / I G It is larger, so it has better kinetic performance, which is beneficial to improving the speed of active ion embedding into the negative electrode film layer, improving the active ion transport performance of the negative electrode film layer, and improving the kinetic performance of the secondary battery; at the same time, when it is located in the second area of ​​the negative electrode film layer, it is also beneficial to give full play to its excellent kinetic performance advantages, and is beneficial to improving the wetting and retention characteristics of the negative electrode film layer to the electrolyte.

[0099] The first carbon-based material has a pore structure and a large compaction density, which can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery; D / I G It is smaller, so it has higher surface stability and lower surface activity, which can reduce the occurrence of side reactions and improve the storage performance of the secondary battery; at the same time, the first carbon-based material also has the advantage of high capacity. When it is located in the first area of ​​the negative electrode film layer, it can give full play to its advantages of high capacity and high compaction density, thereby improving the energy density of the secondary battery.

[0100] Therefore, the negative electrode plate provided in this application can take into account high compaction density, high active ion transport performance and high surface stability, and the secondary battery using the negative electrode plate provided in this application can take into account good dynamic performance and storage performance while having high energy density.

[0101] In some embodiments, the first carbon-based material D / I G With the second carbon-based material I D / I G The ratio A is less than or equal to 0.80, and can be selected from 0.32-0.77 and 0.33-0.70. When α is within the above range, it is beneficial for the secondary battery to better balance good dynamic performance and storage performance while having high energy density.

[0102] In some embodiments, the first carbon-based material D / I G The first carbon-based material has an I of 0.152-0.280, and can be selected from 0.152-0.260, 0.153-0.240, 0.155-0.220, 0.155-0.200, and 0.155-0.180. D / I GWithin the above range, the first carbon-based material may have less disordered carbon, higher specific capacity and higher chemical stability, thereby reducing the occurrence of side reactions and improving the energy density and storage performance of the secondary battery.

[0103] In some embodiments, the second carbon-based material D / I G The second carbon-based material has an I of 0.230-0.500, and can be optionally 0.235-0.450. D / I G When within the above range, the active ion transport performance of the second carbon-based material is better, which is beneficial to improving the kinetic performance of the secondary battery.

[0104] In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is smaller than the volume distribution particle size Dv50 of the first carbon-based material. This facilitates the first and second regions of the negative electrode film layer to have a suitable pore distribution. This improves the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery. Furthermore, it improves the electrolyte wetting and retention properties of the negative electrode film layer, reduces expansion of the negative electrode sheet, and thus improves the storage performance and / or cycle performance of the secondary battery.

[0105] In some embodiments, the powder compaction density of the second carbon-based material under a pressure of 20,000 N is less than the powder compaction density of the first carbon-based material under a pressure of 20,000 N. By adjusting the powder compaction density of the second carbon-based material to be less than the compaction density of the first carbon-based material, on the one hand, it is beneficial to improve the energy density of the secondary battery, and on the other hand, it is beneficial to have a suitable pore distribution in the first region and the second region of the negative electrode film layer, thereby improving the infiltration and retention characteristics of the negative electrode film layer with the electrolyte, thereby improving the dynamic performance and / or cycle performance of the secondary battery.

[0106] In some embodiments, the second carbon-based material comprises at least one of artificial graphite and natural graphite. Alternatively, the second carbon-based material comprises natural graphite.

[0107] In some embodiments, the second carbon-based material has a porous structure.

[0108] In some embodiments, the ratio of the pore area in the cross-section of the first carbon-based material particle to the cross-sectional area of ​​the first carbon-based material particle is denoted as α1, and the ratio of the pore area in the cross-section of the second carbon-based material particle to the cross-sectional area of ​​the second carbon-based material particle is denoted as α2, and α1<α2.

[0109] In the present application, the ratio of the pore area in the cross section of the first carbon-based material particle to the cross-sectional area of ​​the first carbon-based material particle α1 and the ratio of the pore area in the cross section of the second carbon-based material particle to the cross-sectional area of ​​the second carbon-based material particle α2 can be obtained by testing the cross-sectional images of each of the first carbon-based material and the second carbon-based material. For example, a cross-sectional polisher (such as the IB-09010CP argon ion cross-sectional polisher of JEOL, Japan) can be used to prepare a cross section of the first carbon-based material (or the second carbon-based material); then, referring to JY / T010-1996, a scanning electron microscope (such as the Sigma 300 scanning electron microscope of ZEISS, Germany) is used to scan the cross section of the first carbon-based material (or the second carbon-based material); finally, the pore area of ​​the first carbon-based material (or the second carbon-based material) is calculated by image processing software (such as AVIZO), α1 is the ratio of the pore area in the cross section of the first carbon-based material particle to the cross-sectional area of ​​the first carbon-based material particle, and α2 is the ratio of the pore area in the cross section of the second carbon-based material particle to the cross-sectional area of ​​the second carbon-based material particle.

[0110] In some embodiments, the second carbon-based material includes at least one pore with an area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 pore structure.

[0111] In some embodiments, the X-ray diffraction pattern of the first carbon-based material does not have a diffraction peak of the 012 crystal plane of the 3R phase.

[0112] In some embodiments, the second carbon-based material has a diffraction peak of the 3R phase 012 crystal plane in its X-ray diffraction pattern.

[0113] In some embodiments, the second carbon-based material has a diffraction peak of a 3R phase 101 crystal plane in its X-ray diffraction pattern.

[0114] The 3R (Rhombohedral) phase refers to rhombohedral phase crystalline carbon with an ABCABC... stacking structure. Natural graphite usually has many internal defects and includes 3R phase crystalline carbon. For example, the X-ray diffraction pattern usually has diffraction peaks of the 012 and 101 crystal planes of the 3R phase, while artificial graphite usually does not have 3R phase crystalline carbon. For example, its X-ray diffraction pattern usually does not have diffraction peaks of the 012 and 101 crystal planes of the 3R phase.

[0115] The diffraction peak of the 012 crystal plane of the 3R phase corresponds to a 2θ range of 46°-47° in the X-ray diffraction pattern. The diffraction peak of the 101 crystal plane of the 3R phase corresponds to a 2θ range of 43°-44° in the X-ray diffraction pattern.

[0116] The first carbon-based material does not have the diffraction peak of the 3R phase 012 crystal plane, so the first carbon-based material particles have fewer internal defects, which can further reduce the occurrence of side reactions, reduce the irreversible consumption of active ions, and improve the first coulombic efficiency and storage performance of the secondary battery.

[0117] In some embodiments, the first carbon-based material includes at least one pore with an area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 When the first carbon-based material includes a pore structure having the above-mentioned pore area, the pore structure can reserve the required expansion space for its particle volume change, thereby further reducing the risk of particle breakage and generation of new interfaces, thereby reducing the occurrence of side reactions and improving the storage performance of the secondary battery.

[0118] In some embodiments, the first carbon-based material includes an external region and an internal region located inside the external region, wherein the external region refers to a region extending 0.25L from the particle surface of the first carbon-based material to the interior of the particle, L refers to the short axis length of the first carbon-based material particle, the total pore area of ​​the external region is denoted as S1, the total pore area of ​​the internal region is denoted as S2, and S2>S1.

[0119] When the first carbon-based material also satisfies S2>S1, the first carbon-based material further has the following characteristics: the number of pores in the internal region is large and / or the pore size is large, while the number of pores in the external region is small and / or the pore size is small. The pore structure in the internal region of the first carbon-based material can effectively reduce the rolling pressure of the negative electrode plate, effectively reduce particle damage, and reserve the required expansion space for particle volume changes, thereby reducing the risk of particle breakage and the generation of new interfaces, and thus effectively reducing the occurrence of side reactions; the number of pores in the external region of the first carbon-based material is small and / or the pore size is small, thereby making the first carbon-based material particles have a stable structure and avoiding the electrolyte from penetrating into the pore structure inside the first carbon-based material particles as much as possible, thereby further reducing the occurrence of side reactions and reducing the consumption of active ions by the SEI film formation inside the particles. Therefore, when the first carbon-based material also satisfies S2>S1, it can improve the first coulombic efficiency of the secondary battery and further improve the storage performance and / or cycle performance of the secondary battery.

[0120] In some embodiments, 1.5≤S2 / S1≤500, 2≤S2 / S1≤450, 2.2≤S2 / S1≤400, 2.4≤S2 / S1≤300, 2.5≤S2 / S1≤250, 2.6≤S2 / S1≤200, 2.8≤S2 / S1≤150, and 3.0≤S2 / S1≤100. The inventors found in further research that when S2 / S1 also satisfies the above range, the secondary battery can better balance high energy density and good storage performance.

[0121] In the present application, the total pore area S1 of the outer region and the total pore area S2 of the inner region of the first carbon-based material can be obtained by testing a cross-sectional image of the first carbon-based material.

[0122] In the present application, the cross-sectional image of the first carbon-based material includes a cross-sectional image passing through the center of the first carbon-based material particle. "Particle center" refers to the range within a radius of 0.1 μm extending from the geometric center of the particle to the particle surface.

[0123] In this application, the minor axis length of a particle refers to the minimum value when a line connecting two points on the particle surface passes through the geometric center of the particle.

[0124] FIG4 is a schematic diagram of a cross-sectional image of a particle of the first carbon-based material 200 of the present application, and the cross-sectional image passes through the center of the particle of the first carbon-based material 200. As shown in FIG4 , L represents the length of the minor axis of the particle of the first carbon-based material 200, and the region extending from the surface of the particle of the first carbon-based material 200 to the interior of the particle by a distance of 0.25L is the outer region 201, and the region inside the outer region 201 is the inner region 202.

[0125] A cross-section polisher (e.g., an IB-09010CP argon ion cross-section polisher from JEOL, Japan) can be used to prepare the cross-section of the first carbon-based material; then, referring to JY / T010-1996, a scanning electron microscope (e.g., a Sigma 300 scanning electron microscope from ZEISS, Germany) can be used to scan the cross-section of the first carbon-based material; finally, image processing software (e.g., AVIZO) can be used to calculate the total pore area S1 of the outer region and the total pore area S2 of the inner region of the first carbon-based material.

[0126] In some embodiments, the short axis length L of the first carbon-based material particle satisfies L≥6μm, optionally, 6μm≤L≤25μm, 6μm≤L≤20μm, 7μm≤L≤20μm, 8μm≤L≤20μm, 8μm≤L≤18μm, 8μm≤L≤16μm.

[0127] In some embodiments, the area of ​​the pore structure in the outer region of the first carbon-based material is less than or equal to 0.2 μm2 , can be selected to be less than or equal to 0.10μm 2 In further research, the inventors also found that by controlling the area of ​​the pore structure in the outer region of the first carbon-based material within the above range, the outer region of the first carbon-based material can have a dense structure, thereby effectively improving the structural stability of the first carbon-based material, avoiding the electrolyte from penetrating into the pore structure inside the first carbon-based material particles as much as possible, reducing the occurrence of side reactions, and thus effectively improving the storage performance of the secondary battery. Of course, this application does not intend to limit the area of ​​all pore structures in the outer region of the first carbon-based material to be less than or equal to 0.2 μm 2 For example, the area of ​​the pore structure can be controlled to be less than or equal to 0.2 μm by controlling more than 95%, or more than 99%. 2 .

[0128] In some embodiments, the inner region of the first carbon-based material includes at least one area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 The inventors further discovered that by including the aforementioned pore structure in the interior of the first carbon-based material, the rolling pressure of the negative electrode sheet can be effectively reduced, effectively reducing particle damage, and reserving sufficient and stable expansion space for the volume change of the first carbon-based material particles, thereby reducing the risk of first carbon-based material particle breakage. Furthermore, the compaction density of the negative electrode film layer can be increased, thereby improving the energy density of the secondary battery.

[0129] In some embodiments, at least part of the surface of the first carbon-based material has a coating. Optionally, more than 80% of the surface of the first carbon-based material is covered with a coating, and further, 90%-100% of the surface of the first carbon-based material is covered with a coating. In some embodiments, optionally, the coating comprises carbon, for example, amorphous carbon and / or crystalline carbon with a degree of graphitization between 65% and 89%. Thus, the kinetic performance of the secondary battery can be improved.

[0130] Of course, in some embodiments, the surface of the first carbon-based material may not have a coating layer. The first carbon-based material of the present application has a relatively stable surface. When the surface does not have a coating layer, it is beneficial to maintain low side reaction activity and reduce the occurrence of side reactions, thereby further improving the cycle performance and / or storage performance of the secondary battery.

[0131] In some embodiments, at least part of the surface of the second carbon-based material has a coating layer. In particular, natural graphite has a high surface activity, and forming a coating layer on its surface can reduce its surface activity, thereby further improving the storage performance and cycle performance of the secondary battery.

[0132] In some embodiments, more than 80% of the surface of the second carbon-based material is covered with a coating layer, optionally, 90%-100% of the surface of the second carbon-based material is covered with a coating layer. In some embodiments, the coating layer may include carbon, such as amorphous carbon, which is also beneficial to improving the kinetic performance of the secondary battery. The carbon can be formed by carbonization treatment of an organic carbon source. The organic carbon source can be a carbon-containing material suitable for coating known in the art, for example, it can include one or more of coal tar, petroleum asphalt, phenolic resin, coconut shell, etc.

[0133] In some embodiments, the first carbon-based material includes primary particles. Optionally, the amount of the primary particles in the first carbon-based material is greater than or equal to 50%, for example, 50%-100%, 55%-95%, 60%-100%, 65%-90%, 65%-80%, 70%-100%, 75%-90%, 80%-100%, 90%-100%, or 95%-100%. The first carbon-based material contains an appropriate proportion of primary particles, which can give it higher structural stability and reduce the occurrence of side reactions, thereby improving the storage performance of the secondary battery. In addition, it can also increase the compaction density of the negative electrode film layer and increase the energy density of the secondary battery.

[0134] In some embodiments, the first carbon-based material may be composed entirely of primary particles, that is, the primary particles in the first carbon-based material account for 100%.

[0135] In some embodiments, the second carbon-based material includes primary particles. Optionally, the amount of the primary particles in the second carbon-based material is greater than or equal to 50%, for example, 50%-100%, 55%-95%, 60%-100%, 65%-90%, 65%-80%, 70%-100%, 75%-90%, 80%-100%, 90%-100%, or 95%-100%. The second carbon-based material contains an appropriate proportion of primary particles, which can give it higher structural stability and reduce side reactions, thereby improving the storage performance of the secondary battery. In addition, it can also increase the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery.

[0136] In some embodiments, the second carbon-based material may be composed entirely of primary particles, that is, the primary particles in the second carbon-based material account for 100%.

[0137] The inventors further discovered that when the first carbon-based material satisfies one or more of the following conditions on the basis of the above-mentioned design, the performance of the secondary battery can be further improved, such as improving at least one of the energy density, storage performance, kinetic performance and cycle performance of the secondary battery.

[0138] In some embodiments, the specific surface area of ​​the first carbon-based material is less than or equal to 2.1 m 2 / g, optional 1.0m 2 / g-2.1m 2 / g, 1.1m 2 / g-2.0m 2 / g,1.15m 2 / g-1.8m 2 The first carbon-based material has a lower specific surface area, thereby reducing the consumption of active ions by SEI film formation and improving the initial coulombic efficiency and storage performance of the secondary battery.

[0139] In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm, and optionally 10.0 μm-22.0 μm.

[0140] In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-45.0 μm, optionally 16.5 μm-42.0 μm.

[0141] When the volume distribution particle size Dv50 and / or Dv90 of the first carbon-based material is within the above range, it is beneficial to improve the transmission performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the first carbon-based material, reduce the occurrence of side reactions, and improve the storage performance of the secondary battery.

[0142] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is ≤1.55, and can optionally be 0.90-1.50. When the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is within the above range, its particle packing performance is good, which is beneficial for increasing the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial for adjusting the pore distribution of the negative electrode film layer and improving the dynamic performance of the secondary battery.

[0143] In some embodiments, the first carbon-based material has a powder compaction density of 1.65 g / cm3 under a pressure of 20,000 N. 3 -2.0g / cm 3 , optional 1.68g / cm 3 -1.98g / cm 3When the powder compaction density of the first carbon-based material is within the above range, the compaction density of the negative electrode film layer can be increased, thereby increasing the energy density of the secondary battery. This is also conducive to forming a reasonable pore structure between the particles of the negative electrode film layer, thereby improving the active ion and electron transport performance, and thus improving the kinetic performance of the secondary battery.

[0144] In some embodiments, the tap density of the first carbon-based material is 0.85 g / cm 3 -1.30g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 When the tap density of the first carbon-based material is within the above range, it can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery. It is also conducive to forming a reasonable pore structure between the particles of the negative electrode film layer, improving the active ion and electron transport performance, and thus improving the kinetic performance of the secondary battery.

[0145] In some embodiments, the graphitization degree of the first carbon-based material is ≥95.5%, and can be optionally 95.5%-98.0%. When the graphitization degree of the first carbon-based material is within the above range, it is beneficial to improve the energy density of the secondary battery.

[0146] In some embodiments, the gram capacity of the first carbon-based material is ≥355 mAh / g, and can be 355 mAh / g-370 mAh / g. When the gram capacity of the first carbon-based material is within the above range, it is beneficial to improve the energy density of the secondary battery.

[0147] In some embodiments, the X-ray diffraction pattern of the first carbon-based material has a diffraction peak of the 3R phase 101 crystal plane. When the first carbon-based material has a diffraction peak of the 3R phase 101 crystal plane, there may be more active sites on the surface of the first carbon-based material, thereby facilitating the rapid deintercalation of active ions.

[0148] In some embodiments, the adsorption amount of linseed oil by 100g of the first carbon-based material is 30ml-47mL, optionally 33ml-46mL. When the adsorption amount of linseed oil by the first carbon-based material is within the above range, the surface side reaction activity of the first carbon-based material particles is low, thereby reducing the consumption of active ions by SEI film formation; in addition, it is also beneficial for the negative electrode film layer to have a reasonable pore structure, thereby improving the wetting and liquid retention properties of the negative electrode film layer to the electrolyte. Therefore, when the adsorption amount of linseed oil by the first carbon-based material is within the above range, it is beneficial to improve the storage performance and / or dynamic performance of the secondary battery.

[0149] The adsorption capacity of linseed oil by 100g of the first carbon-based material can be tested as follows: 3780.2-2017, weigh a certain mass (for example, 20g) of the dried test sample, place the weighed sample in the mixing chamber of the oil absorptometer, the mixing chamber temperature is 23°C, and the lid is closed; align the oil delivery pipe of the constant-rate burette with the top of the hole in the mixing chamber cover; start the oil absorptometer, the instrument starts to run and linseed oil is added dropwise. As the oil absorption of the sample increases, the mixed material changes from a free-flowing state to a semi-plastic agglomerate, and the viscosity of the mixture continues to increase. The viscosity is transmitted to the torque sensor system of the oil absorptometer. When the added oil causes the semi-plastic agglomerate to reach a preset torque level, the oil absorptometer and the constant-rate burette are automatically closed; read the value corresponding to 70% of the maximum torque of the fitting curve, and use the formula V = (V0 / m) × 100 to calculate the adsorption amount V of 100g of the first carbon-based material on linseed oil, where V0 represents the volume of linseed oil consumed by the sample corresponding to 70% of the maximum torque, in ml; m is the mass of the added sample, in g.

[0150] The inventors further discovered that when the second carbon-based material satisfies one or more of the following conditions on the basis of the above-mentioned design, it can further improve the performance of the secondary battery, such as improving at least one of the energy density, storage performance, kinetic performance and cycle performance of the secondary battery.

[0151] In some embodiments, the specific surface area of ​​the second carbon-based material is greater than or equal to 1.8 m 2 / g, optional 1.9m 2 / g-3.5m 2 / g,1.85m 2 / g-3.50m 2 / g,1.90m 2 / g-3.45m 2 When the specific surface area of ​​the second carbon-based material is within the above range, it is beneficial to reduce the occurrence of side reactions and reduce the consumption of active ions by SEI film formation, thereby enabling the secondary battery to have both high initial coulombic efficiency and good cycle performance and storage performance.

[0152] In some embodiments, the Dv50 of the second carbon-based material is 8.0 μm-15.0 μm, optionally 10.0 μm-15.0 μm. When the volume distribution particle size Dv50 of the second carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the second carbon-based material, reduce the occurrence of side reactions, and improve the storage performance of the secondary battery.

[0153] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is ≤1.65, and can optionally be 0.90-1.65. When the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is within the above range, its particle packing performance is good, which is beneficial for increasing the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial for adjusting the pore distribution of the negative electrode film layer and improving the dynamic performance of the secondary battery.

[0154] In some embodiments, the second carbon-based material has a powder compaction density of 1.60 g / cm3 under a pressure of 20,000 N. 3 -1.95g / cm 3 , optional 1.65g / cm 3 -1.92g / cm 3 When the powder compaction density of the second carbon-based material is within the above range, the compaction density of the negative electrode film layer can be increased, thereby increasing the energy density of the secondary battery. This is also conducive to forming a reasonable pore structure between the particles of the negative electrode film layer, thereby improving the active ion and electron transport performance, and improving the electrolyte infiltration and retention characteristics of the negative electrode film layer, thereby improving the kinetic performance and / or cycle performance of the secondary battery.

[0155] In some embodiments, the tap density of the second carbon-based material is 0.85 g / cm 3 -1.25g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 When the tap density of the second carbon-based material is within the above range, it can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery. It is also conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, improving the active ion and electron transport performance, and improving the negative electrode film layer's electrolyte infiltration and retention characteristics, thereby improving the kinetic performance of the secondary battery.

[0156] In some embodiments, the second carbon-based material has a degree of graphitization of 94.5% to 98.0%, and optionally 95.0% to 97.5%. When the degree of graphitization of the second carbon-based material is within the above range, it is beneficial to improve the active ion transport performance of the negative electrode film layer and also to improve the negative electrode capacity, thereby enabling the secondary battery to achieve both high energy density and good kinetic performance.

[0157] In some embodiments, the gram capacity of the second carbon-based material is 355 mAh / g-372 mAh / g, and optionally 356 mAh / g-370 mAh / g. When the gram capacity of the second carbon-based material is within the above range, on the one hand, the energy density of the secondary battery can be improved, and on the other hand, the second carbon-based material can also have good active ion transport performance, thereby also helping to improve the kinetic performance of the secondary battery.

[0158] In some embodiments, the first active material further comprises a third carbon-based material, wherein the third carbon-based material comprises artificial graphite in a primary particle morphology. The combination of the first and third carbon-based materials facilitates the negative electrode film layer to have a suitable pore structure and enhances the active ion transport performance of the negative electrode film layer.

[0159] In some embodiments, the surface of the primary particle-shaped artificial graphite does not have a carbon coating. Primary particle-shaped artificial graphite has a relatively stable surface. When the surface lacks a coating, it helps maintain low side reaction activity and reduces the occurrence of side reactions, thereby further improving the cycling and storage performance of the secondary battery.

[0160] In some embodiments, the mass proportion of the third carbon-based material in the first active material is less than or equal to 80wt%, and can be optionally 20wt%-70wt%, 30wt%-70wt%, 35wt%-70wt%, 40wt%-70wt%, 30wt%-60wt%, 35wt%-60wt%, 40wt%-60wt%.

[0161] The inventors further discovered that when the third carbon-based material, in addition to meeting the above-mentioned design, further meets one or more of the following conditions, it can further improve the performance of the secondary battery, such as improving at least one of the energy density, storage performance, kinetic performance and cycle performance of the secondary battery.

[0162] In some embodiments, the degree of graphitization of the third carbon-based material is 92.5%-95.5%, and optionally 92.7%-95.5%. When the degree of graphitization of the third carbon-based material is within the above range, it is beneficial to improve the active ion transport performance of the negative electrode film layer, especially the first region, thereby facilitating the secondary battery to achieve both high energy density and good kinetic performance.

[0163] In some embodiments, the powder OI value of the third carbon-based material is 4.5-11.5, optionally 4.5-11.0. The powder OI value of the third carbon-based material is relatively small, and the particles have active ion embedding ports in all directions, which is conducive to quickly receiving active ions from the positive electrode, thereby further improving the dynamic performance of the secondary battery. Moreover, at this time, the homogeneity of the particles of the third carbon-based material is relatively high, which is conducive to dispersing the expansion rate during the embedding of active ions, reducing the volume change and thickness rebound rate of the negative electrode film layer, thereby further improving the cycle performance and storage performance of the secondary battery.

[0164] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the third carbon-based material is ≤1.65, and can optionally be 0.90-1.65. When the particle size distribution (Dv90-Dv10) / Dv50 of the third carbon-based material is within the above range, its particle packing performance is good, which is beneficial for increasing the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also beneficial for adjusting the pore distribution of the negative electrode film layer and improving the dynamic performance of the secondary battery.

[0165] In some embodiments, the volume distribution particle size Dv50 of the third carbon-based material is 12.0 μm-22.0 μm, optionally 13.5 μm-20.0 μm. When the volume distribution particle size Dv50 of the third carbon-based material is within the above range, it is beneficial to improve the transport performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of ​​the third carbon-based material, reduce the occurrence of side reactions, and improve the storage performance of the secondary battery.

[0166] In some embodiments, the specific surface area of ​​the third carbon-based material is 1.0 m 2 / g-2.0m 2 / g, optional 1.05m 2 / g-1.95m 2 / g. The third carbon-based material has a lower specific surface area, which can reduce the consumption of active ions in SEI film formation, reduce the occurrence of side reactions, and improve the first coulombic efficiency and storage performance of the secondary battery.

[0167] In some embodiments, the tap density of the third carbon-based material is 0.95 g / cm 3 -1.25g / cm 3 , optional 1.00g / cm 3 -1.25g / cm 3When the tap density of the third carbon-based material is within the above range, it can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery. It is also conducive to the formation of a reasonable pore structure between the particles of the negative electrode film layer, improving the active ion and electron transport performance, and thus improving the kinetic performance of the secondary battery.

[0168] In some embodiments, the gram capacity of the third carbon-based material is 350 mAh / g-363 mAh / g, and optionally 352 mAh / g-362 mAh / g. When the gram capacity of the third carbon-based material is within the above range, it can improve the energy density of the secondary battery and the active ion transport performance of the negative electrode film layer, thereby improving the kinetic performance of the secondary battery.

[0169] As shown in FIG. 1 to FIG. 3 , the negative electrode film layer 102 further includes a middle region 1023 located between the first region 1021 and the second region 1022 of the negative electrode film layer and having a thickness of 0.4H (H represents the thickness of the negative electrode film layer 102 ).

[0170] In some embodiments, the intermediate region includes the first active material and / or the second active material. For example, as shown in FIG2 , the intermediate region 1023 may be the same in composition as the first region 1021, whereby the first active material is distributed in the thickness direction of the negative electrode film layer 102 within the range from the second surface 102b of the negative electrode film layer to a thickness of 0.7H; or, as shown in FIG3 , the intermediate region 1023 may be the same in composition as the second region 1022, whereby the second active material is distributed in the thickness direction of the negative electrode film layer 102 within the range from the first surface 102a of the negative electrode film layer to a thickness of 0.7H; or, as shown in FIG1 , the intermediate region 1023 includes both the first active material and the second active material. In this case, the intermediate region 1023 includes both a layer structure comprising the first active material and a layer structure comprising the second active material, and the two layer structures may further have a layer interface.

[0171] In some embodiments, the first region of the negative electrode film layer may further include other negative electrode active materials known in the art in addition to the first carbon-based material and the third carbon-based material described above. For example, it may also include a silicon-based material. The silicon-based material can improve the pore structure in the negative electrode film layer, facilitate electrolyte infiltration and retention, and enhance the dynamic performance of the secondary battery. It can also increase the negative electrode capacity, thereby further improving the energy density of the secondary battery. Optionally, the silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy.

[0172] In some embodiments, when the first region of the negative electrode film layer further comprises a silicon-based material, the mass proportion of the silicon-based material in the first region of the negative electrode film layer may be ≤10%, for example, 1%-8%, 2%-6%, or 3%-7%. This improves the kinetic performance and energy density of the secondary battery while also ensuring good cycling performance and storage performance.

[0173] In some embodiments, the second region of the negative electrode film layer may further include other negative electrode active materials known in the art in addition to the aforementioned second carbon-based material. For example, it may also include a silicon-based material. The silicon-based material can improve the pore structure in the negative electrode film layer, facilitate electrolyte infiltration and retention, and enhance the dynamic performance of the secondary battery. It can also increase the negative electrode capacity, thereby further improving the energy density of the secondary battery. Optionally, the silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy.

[0174] In some embodiments, when the second region of the negative electrode film layer further comprises a silicon-based material, the mass proportion of the silicon-based material in the second region of the negative electrode film layer may be ≤10%, for example, 1%-8%, 2%-6%, or 3%-7%. This improves the kinetic performance and energy density of the secondary battery while also ensuring good cycling performance and storage performance.

[0175] In some embodiments, both the first region and the second region include silicon-based materials, and the mass proportion of the silicon-based materials in the first region is less than or equal to the mass proportion of the silicon-based materials in the second region. During the charge and discharge process of the secondary battery, the volume expansion of the silicon-based material is greater than that of the carbon-based material, which is conducive to the second region of the negative electrode film layer having a higher porosity, thereby facilitating the improvement of the wetting properties of the negative electrode film layer to the electrolyte, improving the transport performance of active ions, and improving the cycle performance and / or kinetic performance of the secondary battery. In addition, due to the higher porosity of the second region of the negative electrode film layer, the active ion transport performance of the first region of the negative electrode film layer can also be improved.

[0176] In some embodiments, the middle region of the negative electrode film layer further comprises a silicon-based material.

[0177] In some embodiments, the first region, the second region, and the middle region of the negative electrode film layer may optionally further include a negative electrode conductor and / or a negative electrode binder.

[0178] The present application has no particular limitation on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0179] The present application has no particular restriction on the type of the negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS).

[0180] In some embodiments, the first region, the second region, and the middle region of the negative electrode film layer may further optionally include other additives. For example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0181] In some embodiments, the porosity of the negative electrode film is 18.0%-36.7%, and optionally 19.0%-34.0%. This facilitates the negative electrode film to achieve both high capacity and a suitable pore structure, thereby facilitating the secondary battery to achieve both high energy density and good storage performance and dynamic performance.

[0182] In some embodiments, the compaction density of the negative electrode film layer is 1.45 g / cm 3 -1.90g / cm 3 , optional 1.50g / cm 3 -1.85g / cm 3 This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good storage performance and kinetic performance.

[0183] In some embodiments, the surface density of the negative electrode film layer is 5.0 mg / cm 2 -25.0mg / cm 2 , optional 5.5mg / cm 2 -22.5mg / cm 2 This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good storage performance and kinetic performance.

[0184] In some embodiments, the OI value of the negative electrode film layer is less than or equal to 45.0, and can be 8.0-45.0. This helps improve the active ion embedding performance of the negative electrode film layer and also enables the negative electrode film layer to have a lower thickness rebound rate, thereby facilitating the secondary battery to have good storage performance and dynamic performance.

[0185] In some embodiments, the thickness of the negative electrode film layer is greater than or equal to 60 μm, and can be optionally 70 μm-250 μm, or 90 μm-220 μm.

[0186] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0187] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate described in the present application further includes a protective layer covering the surface of the negative electrode film layer.

[0188] The negative electrode current collector has two surfaces that face each other in the thickness direction, and the negative electrode film is disposed on either or both of the two opposing surfaces of the negative electrode current collector. It should be noted that the negative electrode film parameters (e.g., compacted density, surface density, porosity, OI value, etc.) given in this application refer to the parameters of the negative electrode film on a single side of the negative electrode current collector. When the negative electrode film is disposed on both sides of the negative electrode current collector, the parameters of the negative electrode film on either side satisfy the requirements of this application and are considered to fall within the scope of protection of this application.

[0189] In the present application, whether there is a coating layer on the surface of a material (eg, the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.) can be determined by transmission electron microscopy.

[0190] In this application, the specific surface area of ​​a material (e.g., a first carbon-based material, a second carbon-based material, a third carbon-based material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured using the nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The test instrument can be a Tri-Star 3020 specific surface area pore size analyzer from Micromeritics, USA.

[0191] In this application, the degree of graphitization of a material (e.g., the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.) has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) plane in the crystal structure of the material. 002 Then according to the formula g=(0.344-d 002 ) / (0.344-0.3354)×100% to calculate the degree of graphitization. In the above formula, d 002 It is the average interlayer spacing of the C(002) planes in the material's crystal structure expressed in nanometers (nm).

[0192] In this application, the volume distribution particle size Dv10, Dv50, and Dv90 of the material (e.g., the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.) are well-known in the art, and respectively represent the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0193] In this application, the powder compaction density of a material (e.g., the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured using an electronic pressure testing machine (e.g., a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. An exemplary test method is as follows: Weigh 1 g of sample powder and add a 1.327 cm 2 In the mold, pressurize to 2000kg, maintain pressure for 30s, then release the pressure, maintain for 10s, and then record and calculate the powder compaction density of the material under a pressure of 20000N.

[0194] In this application, the tap density of a material (such as a first carbon-based material, a second carbon-based material, a third carbon-based material, etc.) is a meaning well known in the art and can be measured using instruments and methods known in the art. For example, GB / T5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Baxter BT-301, and the test parameters are as follows: vibration frequency 250 ± 15 times / minute, amplitude 3 ± 0.2 mm, vibration number 5000 times, and graduated cylinder 25 mL.

[0195] In this application, the I of the material (eg, the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.) D / I G Raman spectrometer can be used for testing. D The Raman spectrum of the material is 1350±50cm -1 The D peak intensity at I G The Raman spectrum of the material is 1580±50cm -1 The test conditions are: excitation wavelength 532nm, grating 600 lines, objective lens 50 times, integration time 10s, accumulation times 3 times, surface scanning, obtain the D peak and G peak intensity of 100 points, calculate the I of 100 points D / I G , remove the largest and smallest 30 I D / I G The average value of the remaining 40 points is the I D / I G The testing instrument may be a Horiba LabRAM HR800 Raman spectrometer.

[0196] In this application, the OI value of the powder of the third carbon-based material has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain an X-ray diffraction pattern of the powder sample. According to OI value = I 004 / I 110 Calculate the powder OI value of the sample. 004 is the integrated area of ​​the diffraction peak of the 004 crystal plane of crystalline carbon in the powder sample, I 110 is the integrated area of ​​the diffraction peak of the 110 crystal plane of crystalline carbon in the powder sample.

[0197] In the X-ray diffraction analysis test of this application, a copper target can be used as the anode target, and CuKα rays can be used as the radiation source. The ray wavelength is The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.

[0198] In the present application, the proportion of the number of primary particles in the first carbon-based material (or the second carbon-based material) refers to: randomly taking a test sample in the negative electrode film layer, randomly taking multiple test areas in the test sample, using a scanning electron microscope to obtain images of the multiple test areas, and counting the number of the first carbon-based material (or the second carbon-based material) with primary particle morphology in each image as a proportion of the total number of particles of the first carbon-based material (or the second carbon-based material). The average value of multiple statistical results is the proportion of the number of primary particles in the first carbon-based material (or the second carbon-based material).

[0199] In this application, the gram capacity of materials (such as the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.) has a meaning well known in the art and can be tested using methods known in the art. An exemplary test method is as follows: the sample powder is mixed evenly with the conductive agent carbon black (Super P), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to a concentration of 1 mol / L The electrolyte was then added. A lithium metal sheet was used as the counter electrode, and a polyethylene (PE) film was used as the separator. The cells were assembled into CR2430 button cells in an argon-protected glove box with the electrolyte. The resulting button cells were left to rest for 12 hours, then discharged at a constant current of 0.05C to 0.005V at 25°C. The cells were then left to rest for 10 minutes, and then discharged again at a constant current of 50μA to 0.005V. The cells were left to rest for 10 minutes, and then discharged again at a constant current of 10μA to 0.005V. The cells were then charged at a constant current of 0.1C to 2V, and the charge capacity was recorded. The ratio of the charge capacity to the sample mass is the gram capacity of the corresponding material (e.g., the first carbon-based material, the second carbon-based material, the third carbon-based material, etc.).

[0200] In this application, the areal density of the negative electrode film layer has a meaning well known in the art and can be tested using methods known in the art. For example, a negative electrode sheet coated on one side and cold pressed can be taken (if it is a double-sided coated negative electrode sheet, the negative electrode film layer on one side can be wiped off first), punched into small discs with an area of ​​S1, weighed, and recorded as M1. Then, the negative electrode film layer of the weighed negative electrode sheet is wiped off, and the weight of the negative electrode current collector is weighed and recorded as M0. The areal density of the negative electrode sheet = (M1-M0) / S1.

[0201] In this application, the compacted density of the negative electrode film layer is well known in the art and can be measured using methods known in the art. The compacted density of the negative electrode film layer = the surface density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer is well known in the art and can be measured using methods known in the art, such as using a micrometer (e.g., Mitutoyo 293-100, with an accuracy of 0.1 μm).

[0202] In the present application, the porosity of the negative electrode film layer has a well-known meaning in the art and can be measured using methods known in the art. An exemplary test method is as follows: take a negative electrode sheet that has been coated on one side and cold-pressed (if it is a negative electrode sheet coated on both sides, the negative electrode film layer on one side can be wiped off first), punch it into small disc samples of a certain area, and calculate the apparent volume V1 of the negative electrode sheet; refer to GB / T24586-2009, use an inert gas (such as helium or nitrogen) as a medium, adopt a gas replacement method, and use a true density tester to measure the true volume V2 of the negative electrode sheet. The porosity of the negative electrode film layer = (V1-V2) / V1×100%. Multiple negative electrode sheet samples with good appearance and no powder falling on the edges (such as 30 pieces) can be taken for testing, and the results are averaged, thereby improving the accuracy of the test results. The testing instrument can be a Micromeritics AccuPyc II 1340 true density tester.

[0203] In this application, the OI value of the negative electrode film layer has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain an X-ray diffraction pattern of the negative electrode sheet. According to OI value = I 004 / I 110 The OI value of the negative electrode film layer is calculated. 004 is the integrated area of ​​the diffraction peak of the 004 crystal plane of crystalline carbon in the negative electrode film layer, I 110 The integrated area of ​​the diffraction peak of the 110 crystal plane of the crystalline carbon in the negative electrode film layer. In the X-ray diffraction analysis test of this application, a copper target can be used as the anode target, and CuKα rays can be used as the radiation source. The wavelength of the ray is The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.

[0204] It should be noted that the various parameter tests on the first active material, the second active material, or the negative electrode film layer can be performed by sampling and testing the prepared secondary battery according to the following steps.

[0205] Discharge the secondary battery (for safety reasons, the secondary battery is generally fully discharged). Disassemble the secondary battery, remove the negative electrode, and soak the negative electrode in dimethyl carbonate for a certain period of time (e.g., 2-10 hours). Then remove the negative electrode and dry it at a certain temperature and time (e.g., 60°C for more than 4 hours). After drying, remove the negative electrode. Samples can now be taken from the dried negative electrode to test the aforementioned parameters related to the negative electrode film, such as the surface density, compacted density, porosity, and OI value of the negative electrode film.

[0206] The dried negative electrode sheet is baked at a certain temperature and time (for example, 400°C for more than 2 hours), and a region of the baked negative electrode sheet is selected to sample the second active material first (a blade can be used for powder scraping sampling), and the sampling position is the second region of the negative electrode film layer; then the first active material is sampled in the same way, and the sampling position is the first region of the negative electrode film layer; the collected first active material and second active material are sieved separately (for example, sieved with a 200-mesh sieve), and finally the first active material and second active material samples that can be used to test the various material parameters mentioned above in this application are obtained.

[0207] [Method for preparing negative electrode sheet]

[0208] The present application also provides a method for preparing the negative electrode sheet of the present application. The method comprises the following steps: providing a first slurry containing a first active material and a second slurry containing a second active material; coating the first slurry on the negative electrode current collector, coating the second slurry on the first slurry, and drying and cold pressing to obtain the negative electrode sheet.

[0209] In some embodiments, the first active material, an optional conductive agent, an optional binder, and other optional auxiliary agents may be dispersed in a solvent (eg, deionized water) to form a first slurry.

[0210] In some embodiments, the second active material, an optional conductive agent, an optional binder, and other optional auxiliary agents may be dispersed in a solvent (eg, deionized water) to form a second slurry.

[0211] In some embodiments, the first active material includes a first carbon-based material, or a mixture of a first carbon-based material and a third carbon-based material.

[0212] In some embodiments, the second active material comprises a second carbon-based material.

[0213] In some embodiments, the first slurry and / or the second slurry further comprises a silicon-based material.

[0214] The first slurry and the second slurry can be applied simultaneously at one time or in two separate applications. In some embodiments, the first slurry and the second slurry are applied simultaneously at one time. Applying them simultaneously at one time can reduce the negative electrode film resistance, thereby further improving the kinetic performance and cycle performance of the secondary battery.

[0215] The coating weight of the first slurry and the second slurry can be adjusted according to actual conditions.

[0216] In the present application, the first active material, second active material, etc. mentioned above can be obtained through commercial purchase, or prepared by the following method of the present application.

[0217] In some embodiments, the preparation method of the first carbon-based material includes: step 1, providing a raw material having a plurality of pore structures; step 2, uniformly mixing the raw material and the filler material in a predetermined proportion, then keeping the mixture at a first temperature T1 for a first time t1, and cooling to room temperature to obtain an intermediate; step 3, keeping the obtained intermediate at a second temperature T2 for a second time t2, and obtaining the first carbon-based material.

[0218] In some embodiments, in step 1, the raw material for preparing the first carbon-based material includes natural graphite. Alternatively, the natural graphite includes one or more of flake graphite, natural spherical graphite, and microcrystalline graphite, and more preferably includes natural spherical graphite.

[0219] "Natural spherical graphite" refers to natural graphite with a spherical or quasi-spherical shape, and not all natural graphite particles are controlled to be ideal spheres. In some embodiments, natural spherical graphite with a desired particle size and morphology can be obtained by pre-treating flake graphite. Optionally, the pre-treatment includes crushing, classification, spheroidization, purification, and other processes.

[0220] In some embodiments, in step 1, the graphitization degree of the raw material is ≥94.5%, which is beneficial for adjusting the graphitization degree and interlayer spacing of the first carbon-based material.

[0221] In some embodiments, in step 1, the volume distribution particle size Dv50 of the raw material may be 8.0 μm-25.0 μm, and optionally 10.0 μm-22.0 μm.

[0222] In some embodiments, in step 1, the specific surface area of ​​the raw material may be ≥2.5m 2 / g, optional 2.5m 2 / g-10.0m 2When the specific surface area of ​​the raw material is within the above range, it is beneficial to carry out subsequent filling processing and obtain the first carbon-based material with the required specific surface area. It is also beneficial for the first carbon-based material to have both high capacity and high first coulombic efficiency. In addition, it is also beneficial for the first carbon-based material to have better kinetic properties.

[0223] In some embodiments, in step 2, the softening point temperature of the filling material is 100° C.-170° C. Optionally, the softening point temperature of the filling material is 106° C.-170° C., 106° C.-160° C., 106° C.-152° C., 106° C.-146° C., 106° C.-138° C., 112° C.-160° C., 112° C.-152° C., 112° C.-146° C., or 112° C.-138° C.

[0224] In some embodiments, in step 2, the volume distribution particle size Dv50 of the filler material is less than or equal to 6 μm, and can be 1 μm-6 μm, 1 μm-5 μm, 2 μm-5 μm, or 3 μm-5 μm. This facilitates the filler material to melt under heat and fill into the pore structure of the raw material, and also helps to improve the uniformity of the dispersion of the filler material and the raw material.

[0225] In some embodiments, in step 2, the coking value of the filler material is 20%-48%, and optionally 25%-38%. In this application, the coking value of the filler material is well known in the art and can be measured using instruments and methods known in the art. For example, it can be measured in accordance with GB / T 8727-2008.

[0226] In some embodiments, in step 2, the filling material includes one or more of coal tar, petroleum asphalt, polymer compounds and resins, and may optionally include one or more of coal tar and petroleum asphalt.

[0227] In some embodiments, in step 2, the mass ratio of the filling material to the raw material is (10-40):100, and can be optionally (10-30):100, (10-25):100, (10-20):100, (12-30):100, (12-20):100, (14-28):100, (15-25):100.

[0228] In step 2, by adjusting one or more parameters such as the type, softening point, coking value, and addition amount of the filling material within the above-mentioned range, it is beneficial to adjust the number of pores and / or pore size in the outer and inner areas of the first carbon-based material within a suitable range, which is beneficial to adjust the S2 / S1 of the first carbon-based material within a suitable range.

[0229] By adjusting the type, softening point, coking value, addition amount and other parameters of the filling material within the above range, the viscosity of the filling material is not high after being heated and melted, and it maintains good fluidity. At the same time, it is not easy to adhere to the raw material particles, which can reduce the agglomeration of the raw material particles in the subsequent preparation process. This can also reduce the problems of increased surface defects of the first carbon-based material particles and increased surface active sites due to the need to add a depolymerization process.

[0230] In some embodiments, in step 2, the heating process of uniformly mixing the raw material and the filling material in a predetermined ratio and then heating the mixture to the first temperature T1 is a staged heating process.

[0231] In some embodiments, the staged temperature increasing process includes a first temperature increasing process, a second temperature increasing process, and a third temperature increasing process.

[0232] In some embodiments, the first temperature raising process is to raise the temperature to 200° C.-250° C. and keep the temperature at this temperature for 0.5 h-3 h.

[0233] In some embodiments, the second temperature raising process is to raise the temperature to 450°C-550°C and keep the temperature at this temperature for 0-2 hours. When the holding time is 0 hours, it means that when the temperature is raised to the range of 450°C-550°C, no holding treatment is performed, but the temperature is continued to rise to the first temperature T1.

[0234] In some embodiments, the third temperature raising process is to raise the temperature to the first temperature T1 and keep the temperature at the first time t1.

[0235] In the staged heating process, the temperature is first raised to 200℃-250℃. Since the heating temperature is higher than the softening point of the filling material, the filling material is melted and softened by the heat. Keeping it warm for 0.5h-3h allows it to flow and fill into the pore structure of the raw material; then the temperature is raised to 450℃-550℃. At this time, the melted and softened filling material undergoes a carbonization reaction, gradually forming a semi-coke state and turning into a viscous liquid or solid, thereby preventing the filling material from entering the entire pore structure of the raw material; finally, the temperature is raised to the first temperature. At this time, the filling material undergoes a carbonization reaction, thereby enabling the pore structure occupied by the filling material to be effectively filled.

[0236] In some embodiments, in step 2, the temperature is raised to the first temperature T1 at a rate of 1°C / min-10°C / min. For example, the heating rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any range thereof. Alternatively, the heating rate is 1.5°C / min-8°C / min, 1.5°C / min-6°C / min, 2°C / min-6°C / min, 2°C / min-5°C / min

[0237] In some embodiments, the heating rate of the first heating process may be 1°C / min-10°C / min, optionally 1.5°C / min-8°C / min, 1.5°C / min-6°C / min, 2°C / min-6°C / min, or 2°C / min-5°C / min.

[0238] In some embodiments, the heating rate of the second heating process may be 1° C. / min-10° C. / min, and may be optionally 2° C. / min-8° C. / min.

[0239] In some embodiments, the heating rate of the third heating process may be 1° C. / min-10° C. / min, and may be optionally 2° C. / min-8° C. / min.

[0240] In some embodiments, in step 2, the first temperature T1 is 700° C.-1200° C. For example, the first temperature T1 can be 700° C., 750° C., 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C., 1100° C., 1200° C., or any range thereof. Alternatively, the first temperature T1 is 750° C.-1100° C., 800° C.-1100° C., or 850° C.-1000° C.

[0241] In some embodiments, in step 2, the first time t1 is 1 hour to 5 hours. For example, the first time t1 can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, or any range thereof. Optionally, the first time t1 is 2 hours to 4 hours.

[0242] In some embodiments, in step 2, the heat treatment can be carried out in a device capable of programmed temperature increase, such as a medium frequency furnace, a roller kiln, a rotary kiln, a push plate kiln, a vertical granulation kettle, a horizontal granulation kettle, a vertical reactor, a horizontal reactor or a drum furnace.

[0243] In some embodiments, in step 2, the heat treatment atmosphere may be a protective gas atmosphere, which may include one or more of nitrogen, argon, and helium.

[0244] In step 2, by adjusting one or more of the heating rate, the first temperature, the first time, the heating process, etc. within the above-mentioned range, it is beneficial to adjust the number of pores and / or the pore size in the outer area and the inner area of ​​the first carbon-based material within a suitable range, and it is beneficial to adjust the S2 / S1 of the first carbon-based material within a suitable range.

[0245] In some embodiments, in step 3, the second temperature T2 is 2000° C.-2520° C. Optionally, the second temperature T2 is 2040° C.-2500° C., 2040° C.-2460° C., 2040° C.-2420° C., 2040° C.-2380° C., 2080° C.-2500° C., 2080° C.-2460° C., 2080° C.-2420° C., 2080° C.-2380° C.

[0246] In some embodiments, in step 3, the second time t2 is 1.5 hours to 6 hours. For example, the second time t1 can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, or any range thereof. Optionally, the second time t2 is 2 hours to 5 hours.

[0247] In some embodiments, in step 3, the heat treatment may be performed in a medium frequency furnace, a box-type graphitization furnace, an Acheson graphitization furnace, a continuous graphitization furnace, or an inner-string graphitization furnace.

[0248] In some embodiments, in step 3, the medium frequency furnace and the continuous graphitization heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.

[0249] In step 3, by adjusting one or more of the second temperature and the second time within the above range, it is beneficial to adjust the content of disordered carbon in the first carbon-based material within a suitable range, which is beneficial to adjust the I of the first carbon-based material. D / I G and / or graphitization degree and other parameters are within a suitable range.

[0250] In the preparation method of the first carbon-based material, by adjusting one or more of the parameters of natural graphite, the parameters of the filler material, the heating rate, the first temperature, the first time, the heating process, the second temperature, the second time, etc. within the above range, it is beneficial to adjust the S2 / S1, I D / I G , graphitization degree, gram capacity, specific surface area, particle size, powder compaction density, tap density, linseed oil adsorption capacity and other parameters.

[0251] In some embodiments, the method for preparing the second carbon-based material comprises the steps of: mixing a raw material with an organic carbon source and then carbonizing the mixture to obtain the second carbon-based material. Optionally, the raw material comprises at least one of artificial graphite and natural graphite, and may optionally comprise natural graphite.

[0252] In some embodiments, the organic carbon source may be a carbon-containing material known in the art that is suitable for coating, for example, it may include one or more of coal tar, petroleum asphalt, phenolic resin, coconut shell, etc.

[0253] In some embodiments, the carbonization temperature may be 900°C-1300°C.

[0254] In the preparation method of the second carbon-based material, by adjusting one or more parameters of the raw material parameters (such as particle size, specific surface area, particle size distribution, type, etc.), the amount of organic carbon source added, the carbonization temperature, the carbonization time, etc., it is beneficial to adjust the I of the second carbon-based material. D / I G , graphitization degree, gram capacity, particle size, specific surface area, powder compaction density, tap density and other parameters.

[0255] [Positive electrode]

[0256] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces that are opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.

[0257] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0258] The positive electrode film layer generally includes a positive electrode active material, an optional binder, and an optional conductive agent. The positive electrode film layer is generally formed by coating a positive electrode slurry on the positive electrode current collector and then drying and cold pressing. The positive electrode slurry is generally formed by dispersing a positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0259] The positive electrode active material can adopt positive electrode active materials for secondary batteries well-known in the art.

[0260] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphates may include, but are not limited to, lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds.

[0261] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium-ion battery may include a lithium transition metal oxide having the general formula Li a Ni b Co c M d O e A f and its modified compounds, where 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.

[0262] In some embodiments, as examples, the positive electrode active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 and LiMnPO4.

[0263] In the present application, the modified compounds of the above-mentioned positive electrode active materials may be the ones subjected to doping modification and / or surface coating modification on the positive electrode active materials.

[0264] [Electrolytes]

[0265] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0266] The type of the electrolyte salt is not particularly limited and can be selected according to actual needs.

[0267] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0268] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, for example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE). One or more.

[0269] In some embodiments, the electrolyte may further optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high-temperature performance of the secondary battery, and additives that improve the low-temperature power performance of the secondary battery.

[0270] [Isolation film]

[0271] The present application has no particular limitation on the type of the isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0272] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different.

[0273] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process.

[0274] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0275] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0276] The present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG5 shows a secondary battery 5 with a square structure as an example.

[0277] In some embodiments, as shown in FIG6 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.

[0278] The preparation method of the secondary battery of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, separator, and negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process. The electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. The secondary battery is then vacuum packaged, allowed to stand, formed, and shaped.

[0279] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0280] Figure 7 is a schematic diagram of an exemplary battery module 4. As shown in Figure 7 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0281] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0282] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0283] Figures 8 and 9 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 8 and 9, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 may be arranged in any manner within the battery box.

[0284] The present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0285] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0286] Figure 10 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.

[0287] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.

[0288] Example

[0289] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.

[0290] In the following examples and comparative examples, the first carbon-based material can be prepared by the following method of the present application.

[0291] (1) Preparation of the first carbon-based material

[0292] The flake graphite is mechanically crushed, classified, spheroidized and purified to obtain natural spherical graphite. The obtained natural spherical graphite is mixed with petroleum asphalt, and then the mixed material is placed in a programmable temperature raising device, and the temperature is raised in stages for heat treatment. After the end, it is cooled to room temperature to obtain an intermediate. The obtained intermediate is placed in a graphitization furnace and heat treated. After the end, it is demagnetized and sieved to obtain the first carbon-based material. In the above process, the preparation process of the first carbon-based material given above in this application can be controlled to make the volume average particle size Dv50, S2 / S1, I D / I G The parameters are within the range shown in Table 1.

[0293] The S2 / S1 of the first carbon-based material is obtained by testing using the following method.

[0294] A sample preparation binder and first carbon-based material powder were mixed evenly, then coated onto copper foil and dried at 60°C for 30 minutes before use. The sample was cut into 6 mm x 6 mm pieces and affixed to the sample stage of a CP-type argon ion cross-section polisher. A plasma beam was used to cut the sample to obtain a cross-section of the first carbon-based material, with the cross-section passing through the center of the first carbon-based material particle. The testing instrument can be an IB-09010CP-type argon ion cross-section polisher from JEOL, Japan. The cross-section of the first carbon-based material was scanned using a scanning electron microscope. The test method can refer to JY / T010-1996. The testing instrument can be a Sigma 300 scanning electron microscope from ZEISS, Germany. The area extending 0.25L from the surface of the first carbon-based material particle into the particle interior is designated as the outer area, and the area inside the outer area is designated as the inner area. L represents the minor axis length of the first carbon-based material particle. The total pore area S1 of the outer area of ​​the first carbon-based material and the total pore area S2 of the inner area of ​​the first carbon-based material were calculated using image processing software. The image processing software can be AVIZO.

[0295] In the following examples and comparative examples, the second carbon-based material can be prepared by the following method of the present application.

[0296] (2) Preparation of the second carbon-based material:

[0297] After mixing natural graphite and petroleum pitch, carbonization treatment is carried out at 900℃-1300℃, and then screening is performed to obtain the second carbon-based material. By adjusting the selection of appropriate natural graphite and / or by adjusting one or more parameters such as the amount of petroleum pitch added, carbonization temperature, and carbonization time, the volume distribution particle size Dv50, I D / I G The parameters are within the range shown in Table 1.

[0298] In the following examples and comparative examples, the third carbon-based material can be obtained commercially.

[0299] The secondary batteries of Examples 1-30 were all prepared according to the following method.

[0300] The first carbon-based material (see Table 1 for details), the conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber are thoroughly stirred and mixed in an appropriate amount of deionized water solvent at a weight ratio of 96.4:1:1.2:1.4 to form a first slurry. The second carbon-based material (see Table 1 for details), the conductive agent carbon black (Super P), the thickener sodium carboxymethyl cellulose, and the binder styrene-butadiene rubber are thoroughly stirred and mixed in an appropriate amount of deionized water solvent at a weight ratio of 96.4:1:1.2:1.4 to form a second slurry. The first slurry and the second slurry are extruded simultaneously through a dual-chamber coating device. The first slurry is coated on the negative electrode current collector copper foil, and the second slurry is coated on the first slurry; after drying and cold pressing, the negative electrode sheet is obtained. The coating weight of the first slurry and the second slurry is the same.

[0301] LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) is mixed with carbon black (Super P), a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a weight ratio of 96:2:2. An appropriate amount of NMP solvent is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is then coated on both surfaces of the positive electrode current collector aluminum foil. After drying and cold pressing, a positive electrode sheet is obtained.

[0302] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0303] A polyethylene film is used as an isolation film and is placed in order with the positive electrode sheet and the negative electrode sheet prepared above, so that the isolation film is located between the positive electrode sheet and the negative electrode sheet to play an isolation role. The electrode assembly is then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.

[0304] Comparative Example 1

[0305] The secondary battery of Comparative Example 1 was prepared by a method similar to that of Example 1, except that the coating positions of the first slurry and the second slurry were used. The second slurry prepared in Example 1 was coated on the negative electrode current collector copper foil, and the first slurry prepared in Example 1 was coated on the second slurry prepared in Example 1. After drying and cold pressing, the negative electrode sheet was obtained. The test results are shown in Table 2.

[0306] Example 31

[0307] The secondary battery of Example 31 was prepared using a method similar to that of Example 1, except for the preparation of the first slurry. The first carbon-based material and the third carbon-based material (see Table 3, with a mass ratio of 50:50), a conductive agent, carbon black (Super P), a thickener, sodium carboxymethyl cellulose, and a binder, styrene-butadiene rubber, were thoroughly stirred and mixed in an appropriate amount of deionized water as a solvent at a weight ratio of 96.4:1:1.2:1.4 to form the first slurry.

[0308] Performance Testing

[0309] (1) Fast charging performance test of secondary batteries

[0310] At 25°C, the secondary battery was charged to 4.3V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage. After standing for 5 minutes, the secondary battery was discharged to 2.8V at a constant current of 0.33C, and its actual capacity was recorded as C0.

[0311] Then the secondary battery is charged with constant current at 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0 in sequence to a negative electrode cutoff potential of 4.3V or 0V (whichever is reached first). After each charge, it is discharged to 2.8V at 1C0. The SOC (State of Charge) at different charge rates is recorded. The charge rate-negative electrode potential curve under different SOC states was drawn, and the charge rate corresponding to the negative electrode potential of 0 V under different SOC states was obtained after linear fitting. The charge rate is the charging window under the SOC state, which is recorded as C10% SOC, C20% SOC, C30% SOC, C40% SOC, C50% SOC, C60% SOC, C70% SOC, and C80% SOC, respectively. The charging time T of the secondary battery from 10% SOC to 80% SOC (assuming that the secondary battery does not undergo lithium deposition) is calculated according to the formula (60 / C20% SOC + 60 / C30% SOC + 60 / C40% SOC + 60 / C50% SOC + 60 / C60% SOC + 60 / C70% SOC + 60 / C80% SOC) × 10%, and the unit is min. The shorter the charging time, the better the dynamic performance of the secondary battery.

[0312] (2) Storage performance test of secondary batteries

[0313] At 25°C, the prepared secondary battery was charged at a constant current of 1C to 4.3V, then charged at a constant voltage to a current of 0.05C. After standing for 5 minutes, the secondary battery was discharged at a constant current of 1C to 2.8V. The discharge capacity at this time was recorded, which was the discharge capacity before storage.

[0314] At 25°C, the prepared secondary battery was charged at a constant current of 1C to 4.3V, and then charged at a constant voltage to a current of 0.05C. The secondary battery was then stored in a thermostat at 60°C for 200 days. Capacity retention (%) of the secondary battery after 200 days of storage at 60°C = discharge capacity after storage / discharge capacity before storage × 100%.

[0315] From the results of Tables 1 to 3, it can be seen that by making the first region of the negative electrode film layer include the first carbon-based material, the second region includes the second carbon-based material, the first carbon-based material has a pore structure, and the I of the first carbon-based material D / I G Less than the I of the second carbon-based material D / I G , which enables the battery to have both good dynamic performance and storage performance while having high energy density.

[0316] In the negative electrode film layer of Comparative Example 1, the I D / I G Greater than the I of the second carbon-based material D / I G ,At this time, the battery has poor fast charging capability, poor dynamic performance and poor storage performance.

[0317] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

[0318]

[0319]

Claims

1. A secondary battery comprising a negative electrode plate, wherein: The negative electrode sheet includes a negative electrode current collector and a negative electrode film formed on at least one surface of the negative electrode current collector, the negative electrode film having a first surface away from the negative electrode current collector and a second surface opposite to the first surface, the thickness of the negative electrode film is recorded as H, the area within the thickness range from the second surface of the negative electrode film to 0.3H is recorded as the first area of ​​the negative electrode film, the area within the thickness range from the first surface of the negative electrode film to 0.3H is recorded as the second area of ​​the negative electrode film, the first area includes a first active material, the second area includes a second active material, the first active material includes a first carbon-based material, the second active material includes a second carbon-based material, the first carbon-based material has a pore structure, and the I of the first carbon-based material D / I G Less than the I of the second carbon-based material D / I G , I D Indicates that the Raman spectrum is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum is at 1580±50cm -1 The G peak intensity at .

2. The secondary battery according to claim 1, wherein The first carbon-based material I D / I G With the second carbon-based material I D / I G The ratio A is less than or equal to 0.80, and can be selected as 0.32-0.

77.

3. The secondary battery according to claim 1 or 2, wherein The first carbon-based material I D / I G is 0.152-0.280, optionally 0.155-0.220; and / or, I of the second carbon-based material D / I G It is 0.230-0.500, and can be selected as 0.235-0.

450.

4. The secondary battery according to any one of claims 1 to 3, wherein: The volume distribution particle size Dv50 of the second carbon-based material is smaller than the volume distribution particle size Dv50 of the first carbon-based material.

5. The secondary battery according to any one of claims 1 to 4, wherein: The powder compaction density of the second carbon-based material under a pressure of 20,000 N is less than the powder compaction density of the first carbon-based material under a pressure of 20,000 N.

6. The secondary battery according to any one of claims 1 to 5, wherein: The second carbon-based material includes at least one of artificial graphite and natural graphite; optionally, the second carbon-based material includes natural graphite.

7. The secondary battery according to any one of claims 1 to 6, wherein: The X-ray diffraction pattern of the first carbon-based material does not have a diffraction peak of the 3R phase 012 crystal plane; and / or the X-ray diffraction pattern of the second carbon-based material has a diffraction peak of the 3R phase 012 crystal plane.

8. The secondary battery according to any one of claims 1 to 7, wherein: The second carbon-based material has a pore structure; optionally, the ratio of the pore area in the cross-section of the first carbon-based material particle to the cross-sectional area of ​​the first carbon-based material particle is recorded as α1, and the ratio of the pore area in the cross-section of the second carbon-based material particle to the cross-sectional area of ​​the second carbon-based material particle is recorded as α2, and α1<α2.

9. The secondary battery according to any one of claims 1 to 8, wherein: The first carbon-based material and / or the second carbon-based material comprises at least one pore with an area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 pore structure.

10. The secondary battery according to any one of claims 1 to 9, wherein: The first carbon-based material includes an external region and an internal region located inside the external region, wherein the external region refers to a region extending from the particle surface of the first carbon-based material to the interior of the particle by a distance of 0.25L, and L refers to the short axis length of the first carbon-based material particle. The total pore area of ​​the external region is recorded as S1, and the total pore area of ​​the internal region is recorded as S2, and S2>S1. Optionally, 1.5≤S2 / S1≤500, 2≤S2 / S1≤450.

11. The secondary battery according to claim 10, wherein The area of ​​the pore structure in the outer region of the first carbon-based material is less than or equal to 0.2 μm 2 , can be selected to be less than or equal to 0.10μm 2 and / or, The inner region of the first carbon-based material includes at least one area greater than or equal to 0.15 μm 2 The pore structure may optionally include one or more pores with an area of ​​0.15 μm 2 -2.0μm 2 pore structure.

12. The secondary battery according to any one of claims 1 to 11, wherein: At least part of the surface of the first carbon-based material and / or the second carbon-based material has a coating layer; optionally, the coating layer comprises carbon.

13. The secondary battery according to any one of claims 1 to 12, wherein: The first carbon-based material and / or the second carbon-based material comprises primary particles; Optionally, the amount of the primary particles in the first carbon-based material accounts for greater than or equal to 50%; Optionally, the number of the primary particles in the second carbon-based material accounts for greater than or equal to 50%.

14. The secondary battery according to any one of claims 1 to 13, wherein: The first carbon-based material satisfies at least one of the following conditions: (1) The specific surface area of ​​the first carbon-based material is less than or equal to 2.1 m 2 / g, optional 1.1m 2 / g-2.0m 2 / g; (2) the volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm, and can be optionally 10.0 μm-22.0 μm; (3) the volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-45.0 μm, optionally 16.5 μm-42.0 μm; (4) the particle size distribution of the first carbon-based material (Dv90-Dv10) / Dv50 is ≤1.55, and can be optionally 0.90-1.50; (5) The powder compaction density of the first carbon-based material under a pressure of 20,000 N is 1.65 g / cm 3 -2.0g / cm 3 , optional 1.68g / cm 3 -1.98g / cm 3 ; (6) The tap density of the first carbon-based material is 0.85 g / cm 3 -1.30g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 ; (7) The graphitization degree of the first carbon-based material is ≥95.5%, and can be optionally 95.5%-98.0%; (8) The gram capacity of the first carbon-based material is ≥355 mAh / g, and can be selected from 355 mAh / g to 370 mAh / g; (9) The X-ray diffraction pattern of the first carbon-based material has a diffraction peak of the 101 crystal plane of the 3R phase; (10) The adsorption capacity of linseed oil by 100g of the first carbon-based material is 30ml-47mL.

15. The secondary battery according to any one of claims 1 to 14, wherein: The second carbon-based material satisfies at least one of the following conditions: (1) The specific surface area of ​​the second carbon-based material is greater than or equal to 1.8 m 2 / g, optional 1.9m 2 / g-3.5m 2 / g; (2) Dv50 of the second carbon-based material is 8.0 μm-15.0 μm, optionally 10.0 μm-15.0 μm; (3) the particle size distribution of the second carbon-based material (Dv90-Dv10) / Dv50 is ≤1.65, and can be selected from 0.90 to 1.65; (4) The powder compaction density of the second carbon-based material under a pressure of 20,000 N is 1.60 g / cm 3 -1.95g / cm 3 , optional 1.65g / cm 3 -1.92g / cm 3 ; (5) The tap density of the second carbon-based material is 0.85 g / cm 3 -1.25g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 ; (6) The degree of graphitization of the second carbon-based material is 94.5%-98.0%, and can be optionally 95.0%-97.5%; (7) The gram capacity of the second carbon-based material is 355 mAh / g-372 mAh / g, and can be optionally 356 mAh / g-370 mAh / g; (8) The X-ray diffraction pattern of the second carbon-based material has a diffraction peak of the 3R phase 101 crystal plane.

16. The secondary battery according to any one of claims 1 to 15, wherein: The first active material further includes a third carbon-based material, and the third carbon-based material includes artificial graphite in a primary particle morphology.

17. The negative electrode sheet according to claim 16, wherein: The surface of the artificial graphite in the primary particle morphology does not have a carbon coating layer.

18. The secondary battery according to claim 16 or 17, wherein The mass proportion of the third carbon-based material in the first active material is less than or equal to 80 wt %, and can be optionally 20 wt %-70 wt %.

19. The secondary battery according to any one of claims 16 to 18, wherein: The third carbon-based material satisfies at least one of the following conditions: (1) The degree of graphitization of the third carbon-based material is 92.5%-95.5%, and can be optionally 92.7%-95.5%; (2) The powder OI value of the third carbon-based material is 4.5-11.5, and can be optionally 4.5-11.0; (3) the particle size distribution of the third carbon-based material (Dv90-Dv10) / Dv50 is ≤1.65, and can be selected from 0.90 to 1.65; (4) the volume distribution particle size Dv50 of the third carbon-based material is 12.0 μm-22.0 μm, and can be optionally 13.5 μm-20.0 μm; (5) The specific surface area of ​​the third carbon-based material is 1.0 m 2 / g-2.0m 2 / g, optional 1.05m 2 / g-1.95m 2 / g; (6) The tap density of the third carbon-based material is 0.95 g / cm 3 -1.25g / cm 3 , optional 1.00g / cm 3 -1.25g / cm 3 ; (7) The gram capacity of the third carbon-based material is 350 mAh / g-363 mAh / g, and can be optionally 352 mAh / g-362 mAh / g.

20. The secondary battery according to any one of claims 1 to 19, wherein: The first region and / or the second region further include silicon-based materials; optionally, both the first region and the second region include silicon-based materials, and the mass proportion of the silicon-based materials in the first region is less than or equal to the mass proportion of the silicon-based materials in the second region.

21. The secondary battery according to any one of claims 1 to 20, wherein: An intermediate region located between the first region and the second region includes the first active material and / or the second active material.

22. The secondary battery according to any one of claims 1 to 21, wherein: The negative electrode film layer satisfies at least one of the following conditions: (1) The porosity of the negative electrode film layer is 18.0%-36.7%, and can be optionally 19.0%-34.0%; (2) The compaction density of the negative electrode film layer is 1.45 g / cm 3 -1.90g / cm 3 , optional 1.50g / cm 3 -1.85g / cm 3 ; (3) The surface density of the negative electrode film layer is 5.0 mg / cm 2 -25.0mg / cm 2 , optional 5.5mg / cm 2 -22.5mg / cm 2 ; (4) The OI value of the negative electrode film layer is less than or equal to 45.0, and can be optionally 8.0-45.0; (5) The thickness of the negative electrode film layer is greater than or equal to 60 μm, and can be optionally 70 μm-250 μm.

23. An electrical device comprising the secondary battery according to any one of claims 1 to 22.

Citation Information

Patent Citations

  • Nickel-based active material for lithium secondary battery, preparing method thereof, and lithium secondary battery including positive electrode including same

    CN108183233A

  • Positive electrode active substance for non-aqueous electrolyte secondary battery, method for producing same, and non-aqueous electrolyte secondary battery

    CN109845003A

  • Carbon-silicon composite material with core-shell double-layer substructure and preparation method thereof

    CN110336001A

  • Silicon-based composite negative electrode material, preparation method thereof, and lithium ion battery negative electrode

    CN111224078A

  • Positive electrode active material precursor and preparation method thereof, and positive electrode active material

    CN111370679A

Cited By

  • Negative plate, battery and electric equipment

    CN121237819A